The Implication of Drug Abuse Among Youths - Anieto, Ogochukwu Nwamaka (Teaching, Learning, and Development, 2026)
This study explores the implications of drug abuse among youths, examining its social, health, economic, and legal dimensions. The research highlights commonly abused substances and identifies key causes, including peer pressure, family environment, social media influence, and mental health factors. Socially, drug abuse disrupts family dynamics, damages peer relationships, increases crime and violence, and places a strain on public resources such as healthcare and law enforcement. Health implications encompass significant physical and mental health effects, including organ damage, risk of overdose, cognitive decline, depression, and co-occurring disorders. Economically, drug abuse burdens healthcare systems, leads to productivity losses, and creates long-term financial challenges for families and society. Legally, it results in drug-related crimes and severe consequences for youth offenders, impacting their future prospects. Effective preventive measures are discussed, including educational programs, the role of schools and community organizations, parental involvement, mental health interventions, and government policies. The study also covers treatment and rehabilitation strategies, emphasizing the importance of comprehensive support systems and long-term recovery efforts. This research upheld the need for a coordinated approach to address the complexities of youth drug abuse and foster effective solutions.